Higher Education Students’ Perception on Online Learning during Covid-19 Pandemic - Roudlotun Nurul Laili; Muhammad Nashir (Universitas Pahlawan Tuanku Tambusai, 2021)
Covid-19 pandemic has an impact on the higher education system in Indonesia where lecturers and students have to carry out online teaching and learning process. This study aimed to investigate the higher education students’ perception on online learning during covid-19 pandemic and the supporting factors and constraints during online learning. This study used descriptive method. The total respondents were 103 students of Stikes Banyuwangi who joint Intensive English class in the 2020/2021 academic year. The results indicated that students have positive and negative perceptions on online learning. Online learning offers flexibility but it also presents various constraints such as unstable signal, some students were less motivated, more difficult to practice conversation, and high cost of internet. Mostly students (91%) prefer face to face learning to online learning. In conclusion the important factors in conducting online learning are the availability of supporting tools, stability of internet access, and applications of online learning must be easy to access, attractive, motivating and in the form of combination among several online learning media to provide the best way in delivering and accepting the material during teaching learning process